1999
DOI: 10.1038/44860
|View full text |Cite
|
Sign up to set email alerts
|

Actin-based motility of vaccinia virus mimics receptor tyrosine kinase signalling

Abstract: Studies of the actin-based motility of the intracellular pathogens Listeria monocytogenes and Shigella flexneri have provided important insight into the events occurring at the leading edges of motile cells. Like the bacteria Listeria and Shigella, vaccinia virus, a relative of the causative agent of smallpox, uses actin-based motility to spread between cells. In contrast to Listeria or Shigella, the actin-based motility of vaccinia is dependent on an unknown phosphotyrosine protein, but the underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
424
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(438 citation statements)
references
References 27 publications
14
424
0
Order By: Relevance
“…Recent reports have shown that N-WASP and WASP are involved in actin rearrangements induced by several pathogens. N-WASP is required for the formation of an actin tail by Shigella in the cytoplasm of epithelial cells (Suzuki et al, 1998;Egile et al, 1999), whereas N-WASP (or WASP) is involved in the actin tail formation of vaccinia virus and in the formation of actin pedestal structures beneath enteropathogenic Escherichia coli (EPEC) attached to the host cell (Frischknecht et al, 1999;Kalman et al, 1999). Although the precise mechanisms underlying pathogen-directed cytoskeletal rearrangements remain to be elucidated, studies have clearly indicated that pathogens share similar mechanisms of inducing actin polymerization both to each other and to the host systems, as typically exemplified by the status of N-WASP or Arp2/3 complex in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that N-WASP and WASP are involved in actin rearrangements induced by several pathogens. N-WASP is required for the formation of an actin tail by Shigella in the cytoplasm of epithelial cells (Suzuki et al, 1998;Egile et al, 1999), whereas N-WASP (or WASP) is involved in the actin tail formation of vaccinia virus and in the formation of actin pedestal structures beneath enteropathogenic Escherichia coli (EPEC) attached to the host cell (Frischknecht et al, 1999;Kalman et al, 1999). Although the precise mechanisms underlying pathogen-directed cytoskeletal rearrangements remain to be elucidated, studies have clearly indicated that pathogens share similar mechanisms of inducing actin polymerization both to each other and to the host systems, as typically exemplified by the status of N-WASP or Arp2/3 complex in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…62 and 63). We show here that in T cells, as in shigella, vaccinia, and EPEC (41,42,64), Nck is a component of the WASP/N-WASP signaling complex. The recruitment of Nck to tyrosine phosphorylation sites in SLP-76 parallels the recruitment of Nck to tyrosine phosphorylated sites in the Tir protein of EPEC (42,65) and in the A36R protein of vaccinia (41).…”
Section: Discussionmentioning
confidence: 99%
“…Actin tails or plumes resembling actin comet tails that propel some intracellular pathogens through the cytoplasm have been observed to associate with a variety of endocytic structures (CCSs, endosomes, lysosomes, caveolae, and macropinosomes), and other trafficking vesicles (Heuser and Morisaki, 1992;Frischknecht et al, 1999;Merrifield et al, 1999;Kaksonen et al, 2000;Rozelle et al, 2000;Schafer et al, 2000;Taunton et al, 2000;Kanzaki et al, 2001;Lee and De Camilli, 2002;Merrifield et al, 2002;Orth et al, 2002;Pelkmans et al, 2002). During clathrin-mediated endocysosis, it is now known that actin appears transiently at CCPs just as they begin to move into the cytoplasm (Merrifield et al, 2002).…”
Section: Discussionmentioning
confidence: 99%